Sonoridades beckettianas: a criação vocal do intérprete - Andrade, Manuel Fabricio Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research investigated how some Brazilian performers prepared themselves vocally to play Samuel Beckett’s short theatre. If there was some sort of preparation or not,what kind of problems encountered etc. Seven artists were interviewed who were involved in some Brazilian theatrical productions between the years 1985 and 2012. The result of these conversations gives a sense of how their involvement was with Beckett's work and what kind of impact it had on their relationship with creation particularly with regard to the way the word into the performance. The reports opened possibilities for reflections on the role of the performer in a type of rigorous theater like Beckettian theatre. Understanding how the relationship between body and voice or how they deal with the creation of characters which often does not seem possible within an approach psychological or realistic, but from material aspects of staging such as movement, breathing, sound and vocal scores. Finally, we realized that not there was a vocal specific technical preparation of the performers and the vocal creation was understood as the result of a work which encompasses notions of the commitment of the actor, representation and presentification, the discussions of ways to work the character, rituals of preparation, among others, opening the field to discuss the value of vocal technique in the performance of this kind of theater.

Nesta pesquisa investigamos como alguns artistas envolvidos na encenação de peças curtas do teatro de Samuel Beckett no Brasil lidaram com o trabalho de criação vocal das mesmas, se houve algum tipo de preparo ou não, que tipo de problemas encontraram etc. Foram entrevistados sete artistas que estiveram envolvidos em alguma montagem brasileira entre os anos de 1985 e 2012. O resultado das conversas dá uma noção de como foi o envolvimento deles com a obra beckettiana e que tipo de impacto ela teve na relação deles com a criação, sobretudo no tocante à maneira como a palavra era colocada em cena. Os relatos abriram possibilidades de reflexões acerca do papel do intérprete em um tipo de teatro rigoroso como o de Beckett, de como entendem a relação entre corpo e voz, ou como lidam com a criação de personagens, que frequentemente não parece possível dentro de uma abordagem psicológica ou realista, mas sim a partir de aspectos bem materiais da encenação, como a movimentação, a respiração, a partitura sonora e vocal. Por fim, percebemos que não houve um preparo técnico vocal específico dos artistas consultados e que a criação vocal foi compreendida como a consequência de um trabalho que engloba noções de entrega do ator, de representação e resentificação, discussões sobre formas de se trabalhar a personagem, de rituais de preparação, entre outras, abrindo campo para discutir o valor da técnica vocal no desempenho de tal tipo de teatro.
Keywords: Beckett, Samuel 1906-1989; Teatro; Atores; Criação (Literária, artística, etc.); Voz - Educação; Theater